Proposal of quantitative and qualitative metrics to assess affective user-centered design of video games - Ribeiro, Elison; Seruffo, Marcos (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2018: Anais Estendidos do XVII Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2018.4197, 2018)
The experience which emerges from digital games has, above all, an emotional nature, so evaluating the user experience only through objective factors does not seem to be sufficient for the analysis of a game as it is an entertainment product. This article intends to propose a set of metrics that allow evaluating affective, or roughly speaking, emotional aspects of the user experience from digital games. The metrics are applied to a list, found in a related work, of relevant game design components that affect the subjective experience of gaming. The intended experiment in the future is a gameplay session of a game especially designed to include a system that measures in background, through the proposed metrics, players’ actions in the gaming experience. The result in this paper is a set of quantitative and qualitative metrics that will assess players’ choices in the actual experiment and that yield numerical outcomes, even though the analyzed factors are subjective.